Attention disorders in normal aging, mild cognitive impairment and early Alzheimer's disease - Τσολάκη, Μ.; Κουντή, Φ.; Πέτκαρη, Ε.; Κιοσσέογλου, Γ.; Ξανθούλης, Φ.; Κάζη, Ε.; Διαμαντίδου, Α.; Κάζης, Α.; Ευκλείδη, Α. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF